2022
DOI: 10.1111/febs.16552
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ as a coordinator of skeletal muscle differentiation, fusion and contraction

Abstract: Muscle regeneration is essential for vertebrate muscle homeostasis and recovery after injury. During regeneration, muscle stem cells differentiate into myocytes, which then fuse with pre-existing muscle fibres. Hence, differentiation, fusion and contraction must be tightly regulated during regeneration to avoid the disastrous consequences of premature fusion of myocytes to actively contracting fibres. Cytosolic calcium (Ca 2+ ), which is coupled to both induction of myogenic differentiation and contraction, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…Physiologically, STAC3 oversees the biochemical relationship between calcium sensing (DHPR) and calcium-releasing (RYR1) receptors at the sarcoplasmic reticulum in skeletal muscle 23,46 , with calcium homeostasis being essential for active contractions, tissue formation, maturation, and regeneration 65 . In the present work, stac3 -/larvae were found to have lower concentrations of calcium and upregulation of ryr1a in an early patterning of skeletal muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, STAC3 oversees the biochemical relationship between calcium sensing (DHPR) and calcium-releasing (RYR1) receptors at the sarcoplasmic reticulum in skeletal muscle 23,46 , with calcium homeostasis being essential for active contractions, tissue formation, maturation, and regeneration 65 . In the present work, stac3 -/larvae were found to have lower concentrations of calcium and upregulation of ryr1a in an early patterning of skeletal muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, STAC3 oversees the biochemical relationship between calcium sensing (DHPR) and calcium-releasing (RYR1) receptors at the sarcoplasmic reticulum in skeletal muscle 20,43 , with calcium homeostasis being essential for active contractions, tissue formation, maturation, and regeneration 62 . In the present work, stac3 -/larvae were found to have lower concentrations of calcium and upregulation of ryr1a in an early patterning of skeletal muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, PS that is located in the inner leaflet of the plasma membrane (Balasubramanian & Schroit, 2003) needed to be translocated to the outer leaflet of lipid bilayer to promote fusion of the myoblasts. The subsequent inward translocation of PS by specific phospholipid flippase complex switches on PIEZO1 and allows the entry of Ca 2+ ions that are critical for myotube formation and muscle contraction (Ortuste Quiroga et al, 2022; Sinha et al, 2022; Figure 2). Recently, it was shown that the application of the selective PIEZO1 agonist—Yoda1, leads to PS externalization in red blood cells from patients with sickle cell anemia but, interestingly, external Ca 2+ is not required for PS exposure (Wadud et al, 2020).…”
Section: Regulation Of Piezo1 By Lipidsmentioning
confidence: 99%